Assessment of Different Root Canal Preparation Techniques with Rotary Nickel-Titanium Instruments by Novice Students - Andreas Bartols; David W. Christofzik; Matthias Krummel; Christian Friedrichs; Tim Pousset; Birte Größner-Schreiber; Christof E. Dörfer (MDPI AG, 2018)
This study investigated which preparation strategy for root canals leads to the best technical preparation quality, and moreover, which is perceived to be performed best by novice students. Sixty-four students were recruited to prepare one simulated root canal with each of the following: FlexMaster files (F), Mtwo files (M), and Reciproc files (R). After preparation, the students assessed the different instrument systems through a questionnaire. The technical quality of the root canal preparations was evaluated by the centering ratio of the preparation. A total of 186 prepared root canals were submitted for evaluation. With R, significantly better centered preparations were achieved when compared to M and F (p < 0.001). The students evaluated R faster than M and F, and evaluated F significantly (p < 0.05) slower than R and M. M was rated as the easiest system to learn and to handle, as well as the best at reaching the working length; therefore, it was evaluated as the overall favorite of the students. A difference was found between the students’ perceptions and their achieved technical quality of root canal preparations.